Student’s Social Skills Through the Application of Cooperative Learning Rotating Trio Exchange at Class X MIPA SMA - Ressy Rilianika; Nur Islami; Zulirfan Zulirfan; Yati Gusneli (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2020)
The purpose of this research was to describe the social skills of students in class X MIPA SMA Negeri 5 Pekanbaru, through the application of the rotating trio exchange (RTE) type of cooperative learning model on momentum and impulse material. This type of pre-experimental research with intact-group comparison design. The research subjects were students of class X MIPA 4 and class X MIPA 2, each of which totaled 36 students. The data were obtained from direct observation related to aspects of students' social skills by filling out the observation sheet for five indicators, namely: active listening, taking turns in sharing tasks, asking questions, cooperation, and tolerance. The results showed an increase in students' social skills through the application of the RTE cooperative learning model. The increase occurred in each indicator of students' social skills, where the indicators of active listening were 85.33% high category, taking turns in sharing tasks 86.33% high category, asking questions 66.67% medium category, cooperation 84.67 % high category, and 82.00% tolerance high category. These results indicate that almost all of the observed indicators of students' social skills are in the high category, except the indicators asking questions which are in the medium category. Thus the application of the RTE cooperative learning model, in general, can improve students' social skills well in class X MIPA4 SMA 5 Pekanbaru.